The Development of rental relations in agricultural firms - Horobchuk, T. T.; Chaplyhina, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper investigates problems dealing with land relations in agriculture. The paper considers the peculiarities of land rent in the market ownership forms. The advantages and disadvantages as well as reasons and factors of the land rent development are studied in the work. Structural changes in the land property forms are also analyzed. The ways of rental land relations’ improvement are suggested.